On joint distributions of order statistics arising from random vectors - Gungor, M.; Turan, A. (Eudoxus Press, Llc, 2010)
In this study, the joint distributions of order statistics arising from innid random vectors are expressed. Then, some theorems connecting distributions of order statistics of innid random vectors to that of order statistics of iid random vectors are given.
Keywords: Order statistics; permanent; joint distribution; iid random variable; innid random variable